❤❤
![x = \frac{ \sqrt{p + 2q} + \sqrt{p - 2q} }{ \sqrt{p + 2q} - \sqrt{p - 2q} } x = \frac{ \sqrt{p + 2q} + \sqrt{p - 2q} }{ \sqrt{p + 2q} - \sqrt{p - 2q} }](https://tex.z-dn.net/?f=x+%3D++%5Cfrac%7B+%5Csqrt%7Bp+%2B+2q%7D++%2B++%5Csqrt%7Bp+-+2q%7D+%7D%7B+%5Csqrt%7Bp+%2B+2q%7D++-++%5Csqrt%7Bp+-+2q%7D+%7D+)
Then , show that :
qx² - px + q = 0
_____________________
❎ NO SPAM !!!! ❎
#BE BRAINLY
_____________________
Thanks !! ♥♥
@Sanskriti141
Answers
Answered by
38
Applying Componendo & Dividendo Theoram on Both sides :
⇒
⇒
Squaring on both sides We get :
⇒
Applying Componendo - Dividendo Theoram again on both sides :
⇒
⇒
⇒
⇒ qx² - px + q = 0
Sanskriti141:
I'm not able to understand
Answered by
37
First of all rationalize the value of x given
After rationalising, cancel the common factors
After obtaining the final value of x, find the value of x²
Again cancel the common factors of x² and you will obtain the final value of x²
Then substitute the value of x² and x in the equation
qx² - px + q
Then you will be able to solve.
Refer the attachments.
If the attachment is not clear, kindly increase the brightness of your phone :p
Hope it helps dear friend ☺️✌️
Attachments:
![](https://hi-static.z-dn.net/files/d2f/d342ebc212b0cf6321aeffbab0cb2cc7.jpg)
![](https://hi-static.z-dn.net/files/d3c/e42365740b800ce208987a08a0a76a35.jpg)
![](https://hi-static.z-dn.net/files/d05/7bc092ba40b1b59475e1190c79d02c42.jpg)
Similar questions